鄂霍次克海南部晚第四纪的古海洋学记录 - 孙烨忱; 王汝建; 陈建芳; 高爱国; 李秀珠; 韩贻兵 (2009)
鄂霍次克海是太平洋第二大边缘海,在西北太平洋水文环境中扮演重要角色。综合分析了鄂霍次克海南部T00孔沉积物的多种替代性指标,揭示了鄂霍次克海晚第四纪以来的环境变化受季节性海冰变化、大气循环模式、陆源物质通量和表层生产力的共同影响。对比放射虫CyClAdOPHOrA dAVISIAnA的含量曲线与lr04氧同位素记录,该孔沉积物可划分为氧同位素1-7期,底部年龄约为250kA。C.dAVISIAnA在间冰期的高含量表明鄂霍次克海中层水是北太平洋中层水的主要源区。蛋白石和有机碳的分析显示鄂霍次克海表层生产力在冰消期突然增大,随后在间冰期逐渐下降,冰期普遍较低。C/n比值曲线的分析说明鄂霍次克海的有机质沉积物主要来源于海洋。沉积物粒度的分析揭示鄂霍次克海冰期时陆源粗颗粒含量较低,至冰消期粗颗粒含量突然增加,而在间冰期陆源粗颗粒含量较高。 The Sea of Okhotsk is the second largest marginal sea of the Pacific,and plays a significant role in the hydrology of the northwestern Pacific.We processed and analyzed multi-proxies of the sediment of core T00 from the southern Sea of Okhotsk.The results show that the environmental changes in the Sea of Okhotsk are characterized by a coupled interplay between seasonal sea ice dynamics,atmospheric circulation patterns,terrigenous flux,and surface productivity during late Quaternary.The stratigraphic MIS1 to MIS7 since--250 ka of core T00 has been recognized by comparing the percentage curve of Cycladophora davisiana with the LR04 benthic δ18O stack.The higher percentage of C.davisiana during interglacial intervals indicates that the Sea of Okhotsk is the source region of the North Pacific Intermediate Water Mass.The primary productivity in the southern Sea of Okhotsk,indexed by contents of opal and total organic carbon,is relatively higher during interglacials than during glacials,and increases rapidly during deglacials.The oceanic origin of the organic matters in core T00 is figured out by the C/N ratio analysis.The content of terrigenous coarse grain in the Sea of Okhotsk is lower in glacials than in interglacials and increases rapidly in deglacials. 国家重点基础研究发展规划项目(G2007CB815903);国家自然科学基金项目(40321603;40676030;40576029);高等学校博士学科点专项科研基金(20040247028)